Etnobotani Tumbuhan yang Digunakan Dalam Pengobatan Tradisional di Kecamatan Sinjai Selatan Kabupaten Sinjai Sulawesi Selatan - Nurlaila Sari; Baiq Farhatul Wahidah; Nurkhalis A Gaffar (Jurusan Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2017)
This research is a study of Ethnobotany Plants used in traditional medicine in Sinjai Regency South Sinjai Subdistrict of South Sulawesi with the aim to obtain the data how to obtain medical plants and ways of processing in traditional medicine conducted by sanro of South Sinjai. Further data collection is done by means of structured interviews, observation, documentation, and reference searches. Data from the research results are analyzed further qualitative descriptive according to the purpose of the research will be presented in the form of tables, photos or drawings. The results showed that there are 43 kinds of plants used in traditional medicine. Medicinal plants are grouped into three upon how to get IE grows wild as much as 33plants (76.74%), plants that are deliberately kept as many as 7 plants (16.27%) and are bought as many as 3 plants (6.97%). The way used sanro to cultivate the plant into a drug that is a) a drug that is eaten is eaten raw materials; b) a drug that is drunk: ingredients kneaded and then drink or boiled and then drink; c) use: pasted, and then where it chewed, smeared/scrub on the part of the sick/injured.